UJI DAYA HAMBAT JAMUR ANTAGONIS Trichoderma spp DALAM FORMULASI KERING BERBENTUK TABLET TERHADAP LUAS BERCAK Phytophthora palmivora PADA BUAH KAKAO - Asrul, Asrul (AgriSains, 2009)
The research was carried out at the Laboratory of Plant Disease, Faculty of Agriculture, Tadulako University. A various number of Trichoderma spp tablets was diluted into 10 ml of sterilized water in accordance with the treatment dosages, namely 1, 2, 3, 4, 5, 6 and 7 tablets to form suspension. Each Trichoderma spp suspension mixed with P. palmivora suspension (3 ml) were invested into 30 g of soil, then incubated for 0, 3, 6, 9, 12 and 15 days. As much as 5 g of the soil was inserted into a hole made on cacao and incubated for 3, 6, 9, 12, 15 dan 18 days in a series. Then the size of spotted area on cacao was observed in accordance with the day of incubation period. The research result indicated that the treatment of 4 tablet Trichoderma spp has the largest inhibiting power (99,99%), but it was not significantly different with the treatments of 5, 6 and 7 tablets.